THE USE OF LASER THERAPY/ PHOTOBIOMODULATION IN THE MANAGEMENT OF AGING IN OROFACIAL HARMONIZATION: NARRATIVE LITERATURE REVIEW - Brasil , Juliana Arioli Nieto; Carlos Menezes Blasca, Joao; Pilon Muknickas, Daniella; Ribeiro Marques, Brenda; Teodora Ribeiro, Eunice; Teruo Suguihara, Roberto (Health and Society, 2023)
The biophotonic therapies produced by LASERS/LED (low intensity), have aroused great interest in the area of Orofacial Harmonization. These therapies promote important beneficial biological effects, analgesic, anti-inflammatory character through a biostimulation phenomenon. The radiation emitted by therapeutic LASER/LED affects the metabolic processes of target cells, producing biostimulating effects that result in the occurrence of cellular and vascular events, which directly interfere with the tissue repair process. Thus, this work aims to review the literature and demonstrate a clinical case, highlighting the biostimulating effects of LASERS/LED (low power) on tissue repair and their associations in aging management, providing better results for Orofacial Harmonization.